2014
DOI: 10.1139/cjm-2013-0675
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and formulation of antagonistic bacteria for the management of seedlings damping-off and root rot disease of cucumber

Abstract: Antagonistic bacteria are common soil inhabitants with potential to be developed into biofungicides for the management of seedling damping-off, root rot, and other soil-borne diseases of various crops. In this study, antagonistic bacteria were isolated from a commercial potato field and screened for their growth inhibition of fungal and oomycete pathogens in laboratory tests. The biocontrol potential of the 3 most effective antagonistic bacteria from the in vitro tests was evaluated against seedling damping-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 61 publications
2
39
0
3
Order By: Relevance
“…A recent study have shown 27%-50% suppression of Pythium damping-off and root rot of cucumber seedlings along-with 113%-184% increase in plant fresh weight by combined application of two Pseudomonas spp. and B. subtilis [41]. But the inoculation of B. subtilis RMB7 alone resulted in 400-600 folds increase in plant biomass and >85% disease suppression in Arugula plants showing extensively high potential for disease control as well as plant growth promotion.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study have shown 27%-50% suppression of Pythium damping-off and root rot of cucumber seedlings along-with 113%-184% increase in plant fresh weight by combined application of two Pseudomonas spp. and B. subtilis [41]. But the inoculation of B. subtilis RMB7 alone resulted in 400-600 folds increase in plant biomass and >85% disease suppression in Arugula plants showing extensively high potential for disease control as well as plant growth promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Pada benih kacang tanah P. fluorescens memerlukan waktu untuk menunjukkan peningkatan populasi P. fluorescens di rizosfer kacang tanah, seiring dengan meningkatnya umur tanaman (Meena, 2011). Begitu pula aplikasi formula P. fluorescens pada benih tanaman kapas efektif mengendalikan penyakit rebah kecambah pada bibit kapas (62,5%) (Ardakani et al, 2010), dan aplikasi P. fluorescens 9A-14 dan Pseudomonas sp 8D-45 dalam formula bentuk talk pada benih tanaman ketimun efektif mengendalikan penyakit rebah kecambah dan busuk akar bibit (Pythium sp) ketimun dengan tingkat pengendalian 61,04% (Khabbaz and Abbasi, 2014). Berarti efektifitas kombinasi P. fluorescens Pf19 dan Pf101 untuk menekan patogen juga ditentukan oleh umur tanaman.…”
Section: Perkembangan Penyakitunclassified
“…P. fluorescens dapat berperan sebagai Plant Growth Promoting Rhizobacteria (PGPR) yang berasosiasi dengan akar tanaman, menghasilkan senyawa auksin, giberalin dan sitokinin (Landa et al, 2002), senyawa pelarut fosfat dan IAA (Ramyasmruti et al, 2012), efektif memacu pertumbuhan tanaman (Van Loon, 2007dalam Khaeruni et al, 2013. Aplikasi formula talk P. fluorescens 9A-14, Pseudomonas sp 8D-45 dan Bacillus subtilis B-1 (antagonistik) pada benih ketimun efektif meningkatkan pertumbuhan tanaman (Khabbaz and Abbasi, 2014). Formula P. fluorecsens dan B. subtilis pada benih kapas efektif meningkatkan perkecambahan benih dan pertumbuhan bibit (Ardakani et al, 2010).…”
Section: Pertumbuhan Tanamanunclassified
See 1 more Smart Citation
“…are important based on its ability to aggressive colonizers of the rhizosphere of various crops and synthesize several metabolites that are inhibitors of some enzymes or membrane proteins and exert an antagonistic effect (Schippers et al 1987). In addition, nonpathogenic bacteria, fungi, and Actinomycetes belonging to the genera Trichoderma, Fusarium, Streptomyces, and Serratia have been used as potential biocontrol agents against damping-off and root rot pathogens, and other soil-borne pathogens (Someya et al 2003;Minerdi et al 2009;Khabbaz and Abbasi 2014).…”
Section: Introductionmentioning
confidence: 99%